Effect of Procal Lime on the Growth and Results of Cucumber (Cucumis sativus L.) - Heryanto Tato; Musadia Afa; Djunarlin Tojang (Universitas Sembilanbelas November Kolaka, 2017)
The results showed that giving doses of procal lime 4,6875 Kg/swath (Ca3) shows the length of the longest plants i.e. 94,83 cm, the number of leaves by administering a dose of lime procal 4,6875 Kg/swath (Ca3) show the number of leaves that most namely 26,78 strands, the age of the plants start flowering by administering a doses of procal lime 4,6875 Kg/swath (Ca3) speed up the start of flowering plants age i.e. 26,78 (days after planting), the age of the plants begin to bear fruit by administering doses procal lime 4,6875 Kg/swath (Ca3) accelerating the age of the plants start fruiting i.e. 29,33 (days after planting), the amount of fruit plants by administering a doses of procal lime 4,6875 Kg/swath (Ca3) show the number of the most plant fruits namely 12,44 and the weight of the fruit plants by administering a doses of procal lime 4,6875 Kg/swath (Ca3) show the weight of the heaviest fruit i.e. 0,55 Kg